Diet and physical activity in patients with type 1 diabetes - Iafusco, Dario (Acta Biomedica Atenei Parmensis, 2010)
Patients with type 1 diabetes require adequate amounts of macronutrients to support their training and sustain performance during regular exercise and during competitions. A frequent goal in competitive sports is to improve performance, and athletes may resort to a number of practices that can adversely affect blood glucose control and health in general in an attempt to gain a competitive advantage. These may include unsafe dietary patterns, and the use of nutritional supplements, other ergogenic aids and illegal substances. In this paper we review data on the relationship between insulin therapy and needs of single macronutrients before, during and after regular and competitive exercise in young subjects and athletes with type 1 diabetes.We also list nutrition integrators, available in the gymnasium or as over-the-counter drugs, which are increasingly being used by athletes, and describe their interactions with diabetes.